2022
DOI: 10.3390/min12050604
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Modification of CaF2-SiO2-Al2O3-MgO Flux Applied in the Aluminium-Assisted Transfer of Titanium in the Submerged Arc Welding of Carbon Steel: Process Mineralogy and Thermochemical Analysis

Abstract: Flux formulations are specified to target chemical and physico-chemical parameters. Chemical parameters set flux element transfer behaviours and weld metal oxygen contents. Physico-chemical parameters such as slag viscosity, surface tension and melting range are targeted to ensure an acceptable weld bead profile and surface appearance. Slag detachability is an important physico-chemical property required to ensure high welding productivity, smooth weld bead surface and no slag entrapment. Here, bead-on-plate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
6
8
0
Order By: Relevance
“…The pick-up of silicon and manganese in the MP8 weld metal relative to the base case (BC) weld metal analysis is confirmation that sufficient contact time was established between the aluminium powder and the flux to enable reactions ( 5) and ( 6) to proceed to a significant extent. The Al 2 O 3 formed as the product in reactions ( 5) and ( 6) was easily absorbed into the molten flux because these reactions occurred at the molten flux-weld pool interface [31][32][33][34][35][36][37][38]. In order to calculate the exothermic reaction heat contributions from Equations ( 5) and ( 6), the mass of manganese and silicon added to the weld metal via these reactions must first be quantified using Equation ( 9).…”
Section: Exothermic Reactions Quantifiedmentioning
confidence: 99%
“…The pick-up of silicon and manganese in the MP8 weld metal relative to the base case (BC) weld metal analysis is confirmation that sufficient contact time was established between the aluminium powder and the flux to enable reactions ( 5) and ( 6) to proceed to a significant extent. The Al 2 O 3 formed as the product in reactions ( 5) and ( 6) was easily absorbed into the molten flux because these reactions occurred at the molten flux-weld pool interface [31][32][33][34][35][36][37][38]. In order to calculate the exothermic reaction heat contributions from Equations ( 5) and ( 6), the mass of manganese and silicon added to the weld metal via these reactions must first be quantified using Equation ( 9).…”
Section: Exothermic Reactions Quantifiedmentioning
confidence: 99%
“…The exothermic reduction of FeO in the slag by the added Al de-oxidiser element powder was confirmed in previous similar works. Additionally, these works confirmed that the slag FeO content is associated with the level of the oxygen potential at the weld pool-slag interface [34,35]. Similar to FeO aluminothermic reduction, chromium oxide can be reduced by aluminium via Equation ( 5) [12].…”
Section: Weld Metal Chemistrymentioning
confidence: 52%
“…In addition, the aluminothermic reduction reactions in Equations ( 4) and ( 5) are also considered possible, although the extent of these reactions is less clear than that of the reactions in Equations ( 2) and (3). It was confirmed from our previous similar works on different metal powder combinations with aluminium, that FeO is formed from oxidation of iron by the excess oxygen transferred from the arc cavity [37,38]. This FeO may also be reduced by aluminium powder via reaction (4) to control the oxygen potential at the weld pool-slag interface [26][27][28][29][30][31][32][33].…”
Section: Weld Metal Analysesmentioning
confidence: 69%
“…EDX (energy dispersive X-ray) analyses were used to map the elements in the area at the weld metal-slag interface. The major phases in the post-weld slags that formed from aluminium assisted welding with the aluminate basic flux were identified previously as spinel crystals (MgAl2O4) embedded in an oxy-fluoride glass matrix phase [34,37,38]. The slag area displayed in the BSE (backscattered electron) image in Figure 5a was analysed by EDX as displayed in Figure 5b.…”
Section: Chromium and Cobalt Speciation And Distribution In The Slagmentioning
confidence: 98%
See 1 more Smart Citation